Atividade hemaglutinante de amostras do vírus da bronquite infecciosa das galinhas isoladas no Estado de Minas Gerais - Marcelo Tafuri Paniago (1994)
Fourteen strains of avian infectious bronchitis virus isolated from outbreaks of clinical disease in Minas Gerals State, Brazil, were concentrated by dialysis against polyethylene glycol (20.000 MW) and treated with phospholipase C type 1. Among the investigated strains, thirteen showed hemagglutinating activity. These strains were tentatively classified by cross reaction hemagglutlnation-inhibition (HI) test using as antisera, ascitic fluids from Balb-C mice immunized with concentrates of the thirteen strains. The individual immune ascitic fluids did not show HI activity. Not even after the purification of the gammaglobulln fraction from homologous ascitlc fluid with the utilization of ammonium sulfate was possible to detect the presence of HI antibodies. It was not possible to group the strains by this method.